Tunable ultraviolet laser induces high signal-to-noise ratio in intrinsic fluorescence titration for protein- ligand interaction studies - Jean-François Thériault; Lingyao Yu; Preyesh Stephen; Yunlong Sheng; Sheng-Xiang Lin (Results in Physics, 2023)
Protein intrinsic fluorescence emitted by tryptophan residues is widely used for macromolecular mechanism studies, such as the protein binding by ligands and enzyme kinetics. However, modifications in fluorescence intensity can be weak using the intrinsic fluorescence in many proteins containing few tryptophan residues, or with their weak involvement in the binding. A low signal to noise ratio is a main drawback, due to the weak intensity of Xenon lamp illumination in the spectrofluorometer at the ultraviolet (UV) range, in addition to the small intrinsic fluorescence modifications with ligand binding, in many cases. We report herein the montage and the utilization of a laser light source in a spectrofluorometer in the UV range for the titration of protein intrinsic fluorescence. A significantly stronger modification of the protein intrinsic fluorescence was obtained with the titrations represented by E. coli Arginyl tRNA synthetase and human 17β-hydroxysteroid dehydrogenase type 7 with their natural ligands using a wavelength-tunable UV laser source. Also, a higher signal to noise ratio was obtained with the laser source. Finally, a similar KD was obtained with the titration using the two light sources. These results are supported by the direct binding study of equilibrium dialysis, showing that the laser source yields a reliable binding analysis. Thus, the utilization of a laser source in the intrinsic fluorescence titration and related usage can give a significant opening for the wider applications of the spectroscopy and photo technology to many new proteins with limited intrinsic fluorescence signals, while their mechanisms are critical to understand biochemistry and will facilitate medical applications. This study includes fundamental, applied, and interdisciplinary areas of physics.